Productivity, Real Wages, and Economic Growth: A Comment - Ezekiel, Mordecai (Quarterly Journal of Economics, 1961)
Journal Article Productivity, Real Wages, and Economic Growth: A Comment Get access Mordecai Ezekiel Mordecai Ezekiel Food and Agriculture Organization of the United Nations Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 2, May 1961, Pages 314–318, https://doi.org/10.2307/1884205 Published: 01 May 1961